ChemInform Abstract: Experimental and First‐Principles Studies of the Ternary Borides Ta3Ru5B2 and M3‐xRu5+xB2 (M: Zr, Hf). Issue 34 (26th August 2014) - Hermus, Martin; Fokwa, Boniface P. T.
Abstract The ternary borides Ta3Ru5B2, Zr2.86Ru5.14B2, and Hf2.83Ru5.17B2 are synthesized by arc‐melting of stoichiometric mixtures of the elements (Ar, Cu crucibles).